Cities and armed conflict: A systematic urban-rural coding of UCDP conflict events data - Emma Elfversson (Elsevier, 2021)
This data article provides a descriptive overview of the Cities and Armed Conflict Events (CACE) dataset and the data collection methods. The dataset provides a systematic coding of armed conflict events taking place in cities and outside cities across the globe. It constitutes an extension of the Uppsala Conflict Data Program (UCDP) Georeferenced Events Dataset (GED) version 18.1 and covers 1989–2017. To identify which events of armed conflict took place in cities, the data was manually matched to to data from the United Nations Statistics Division (UNSD). The dataset enables systematic analysis of urban-rural patterns in armed conflict, as illustrated by Elfversson & Höglund [1]. While existing methods for analysing such patterns frequently rely on matching conflict data to spatial grids combined with population density, the data presented here with higher validity captures whether violent events take place in cities.